2018
DOI: 10.1016/j.anifeedsci.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of di-peptide dl -methionyl- dl -methionine in comparison to dl -methionine in weaned and growing pigs

Abstract: The relative bioavailability (RBV) of a dipeptide DL-methionyl-DL-methionine (DL-Met-Met) was compared with DL-methionine (DL-Met) in growing pigs (experiment 1; N-balance study) and in weaned pigs (experiment 2; performance study). In experiment 1, 42 barrows with an initial body weight (BW) of 21.0 ± 1.37 kg were assigned to 7 dietary treatments with 6 replicate/pigs per treatment in a nitrogen (N) balance study to evaluate the RBV of DL-Met-Met to DL-Met. A basal diet (BD) was formulated to be adequate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Relevant studies have shown that dl -Met-Met is mainly transported and absorbed by the oligopeptide transporter 1 (PepT1) and oligopeptide transporter 2 (PepT2) transporters in the intestinal epithelium, which does not occupy the absorption channels of other monomeric amino acids and is not easily saturated [17,18]. dl -Met-Met was also found to be more bioavailable and more efficient than dl -Met [19,20]. Although some functions of dl -Met-Met are similar to those of monomeric dl -Met and the overall effect is better, whether dl -Met-Met also acts as a precursor of antioxidant substances to improve muscle quality warrants further study.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that dl -Met-Met is mainly transported and absorbed by the oligopeptide transporter 1 (PepT1) and oligopeptide transporter 2 (PepT2) transporters in the intestinal epithelium, which does not occupy the absorption channels of other monomeric amino acids and is not easily saturated [17,18]. dl -Met-Met was also found to be more bioavailable and more efficient than dl -Met [19,20]. Although some functions of dl -Met-Met are similar to those of monomeric dl -Met and the overall effect is better, whether dl -Met-Met also acts as a precursor of antioxidant substances to improve muscle quality warrants further study.…”
Section: Introductionmentioning
confidence: 99%
“…Met-Met, as novel nutritional supplements for aquatic and terrestrial animals, has attracted much attention in recent years. Reports concerning aquatic and terrestrial animals have indicated that the dietary supplementation with Met-Met can improve the growth performance of organisms (5,17,18,36) . Su et al indicated that dietary Met-Met supplementation increased PWG, SGR and feed efficiency in C. idella (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, compared with the uptake of free methionine, the uptake of Met-Met by dipeptide transporters located on the cell membrane is more efficient [ 10 , 11 ], as evidenced by a study that Met-Met could provide two free methionine for the synthesis of milk protein in mammary gland tissue explants [ 12 ]. Furthermore, Met-Met can be absorbed by cells independent of free methionine and is more stable in water than free methionine, thus it is widely used in aquatic animals [ 13 ]. For example, compared with free methionine, Met-Met is better absorbed to improve fish intestinal immune function [ 14 ].…”
Section: Introductionmentioning
confidence: 99%